Effects of dietary genistein on nutrient use and mineral status in heat-stressed quails - Şahin, Nurhan; Şahin, Kazım; Onderci, M; Sarkar, FH; Doerge, D; Prasad, A; Küçük, Ömer (Int Press Editing Centre Inc, 2006)
Genistein is a powerful antioxidant and plays a role in calcium and bone metabolism. We evaluated the efficacy of dietary supplementation with genistein on the nutrient use and mineral concentrations in tibia and serum of quails reared at high environmental temperature (34 degrees C). Two hundred and forty Japanese quails (10 days old) were randomly assigned to 8 treatment groups consisting of 10 replicates of 3 birds. The birds were kept in a temperature-controlled room at 22 degrees C (Thermoneutral, TN groups) or 34 degrees C (for 8 h/d; 09.00 am-05.00 pm; Heat stress, HS groups). Birds were fed either a basal diet (TN and HS) or the basal diet supplemented with 200, 400 or 800 mg of genistein/kg of diet. Heat exposure decreased apparent nutrient digestibility and bone mineralization when the basal diet was fed (P < 0.001). Apparent digestibility of dry matter (DM) (P < 0.05), crude protein (CP) (P < 0.05) and ash (P < 0.01) was significantly improved by genistein supplementation. However, this improvement was not in direct proportion to increased doses of supplement since there was no difference when diets included either 400 or 800 mg genistein/kg of diet (P < 0.05) in birds reared under heat stress. The amounts of Ca, P, Mg, Mn, Zn, Fe and Cu in the excreta decreased (P < 0.01), while Ca, P, Mg, Mn, Zn and Cu concentrations in tibia ash increased in quails reared under heat stress conditions (P < 0.01) with genistein supplementation. Ca and P concentrations in tibia ash were also increased in birds kept under thermoneutral conditions with genistein supplementation. Increased serum alkaline phosphatase activity (P < 0.01) was associated with increasing dietary genistein in all groups. In conclusion, genistein supplementation to the basal diet improved digestibility of CP, DM and ash and levels of Ca and P and bone mineralization in quails reared under heat stress conditions.
Keywords: bone; digestibility; genistein; quail; stress